From video summarization to real time video summarization in smart cities and beyond: A survey - Shambharkar, Prashant Giridhar; Goel, Ruchi (Frontiers in Big Data, 2023)
With the massive expansion of videos on the internet, searching through millions has become quite challenging. Smartphones, recording devices, and file sharing are all examples of capturing massive amounts of real-time video. In smart cities, many surveillance cameras have created a massive volume of video data whose indexing, retrieval, and administration is a complex problems. Exploring such results takes time and degrades the user experience. In this case, video summarization is extremely useful. Video summarization allows for storing, retrieving, and browsing vast amounts of information from video without sacrificing essential features. This article presents a classification and analysis of video summarization approaches, focusing on real-time video summarization (RVS) domain techniques that can be used to summarise videos. Video summarization has been effectively deployed in smart cities in real-world applications like abnormal detection in a video surveillance system. The current study will be helpful in integrating essential research findings and data for quick reference, laying the preliminaries, and investigating future research directions.